Pengaruh Brand Trust dan Brand Loyalty terhadap Repurchase Intention pada Produk Cat Avian di Gresik - Freddy Cahyadi; Harsono Teguh; Bambang Karnain; Rina Dewi; Achmad Daengs GS (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
. With the development of the era that is increasingly advanced, companies need to make effective marketing plans to excel in business competition. In marketing planning there are several factors that are considered such as Brand Trust and Brand Loyalty that affect Repurchase Intention. The purpose of the study was to determine the effect of brand trust and brand loyalty partially and simultaneously on repurchase interest in Avian paint product customers in Gresik. The type of research used in this study is explanatory research. This study uses a quantitative approach. The sample population was 100 consumers of Avian paint products in Gresik. The method used in sampling was non-probability sampling and purposive sampling techniques. The research instrument used a questionnaire. The data analysis technique used was multiple linear regression analysis. The results of the analysis can be concluded that brand trust has a partial effect on repurchase interest; and brand loyalty has a partial effect on repurchase interest; while Brand Trust and Brand Loyalty have a simultaneous effect on Repurchase Interest in Avian Paint Product Customers in Gresik